Integrated reforms of indirect taxes in the presence of pollution - Michael S. Michael; Sajal Lahiri; Panos Hatzipanayotou (Center for Economic Studies and ifo Institute (CESifo), 2008)
The literature on indirect tax reforms in pollution-ridden economies is quite limited. This paper, using a model of a small open economy with production and consumption generated pollution, considers the welfare implications of tax reforms within an integrated structure of consumption and production taxes. Specifically, both in the presence and absence of a binding government revenue constraint, we derive sufficient conditions for welfare improvement in the case where we implement (i) reforms in either production or consumption taxes, (ii) reforms in both consumption and production taxes and (iii) uniform changes in consumption taxes.
Keywords: H21; H23; 330; indirect tax reforms; production and consumption generated pollution; welfare; government tax revenues; Indirekte Steuer; Steuerreform; Ökosteuer; Kleines-offenes-Land; Umweltökonomik; Wohlfahrtseffekt; Theorie